Freedom of speech and expression in Malaysia: protection under the federal constitution - Mia, Md. Tuhin; Islam, Md. Zahidul; Norullah, Md. (University of Malaya, 2022)
This study aims to understand the position of freedom of speech and expression and the right to freedom of speech in Malaysia stipulated in the Federal Constitution, the controversy over restrictions on freedom of speech, and the issues that hinder freedomof speech from being fully practised. Therefore, this study focuses on the extent of freedom of speech and expression under the Federal Constitution of Malaysia. This study employs qualitative analysis based on secondary data collection. The findings indicate that the Constitution does promote the right to freedom of speech and expression, and it is included in Article 10 of the Federal Constitution of Malaysia, which allows only its citizens to exercise.Freedom of speech and expression does not have any general structure and is notoriously known by others, such as national safety issues, public well-being, and good impulses. Nonetheless, this study lacks the analysis of present position of free speech and hate speech in Malaysia.However, the right to free speech is a fundamental part of human beings and in the establishment of a free society. This study emphasizes theimportance of informationin various platforms such as socialmedia for citizens and the limitations of their freedom of speech and expressions.